THE DYNAMICS OF INNOVATION STRATEGIES IN EUROPEAN ECONOMIES - Stankevice, Inga; Zemite, Lelde (European Scientific Journal, ESJ, 2015)
Innovation is closely related to economic behavior and progress that is often path dependent. This paper provides the evidence of how enterprises’ strategies for innovation changed in the context of external changes, i.e. what kind of changes occurred in innovation strategies of European enterprises since the pre-crisis period and how these changes are related to broader environment. For this purpose, CIS6 micro data from 16 economies and CIS8 macro data from 22 economies were processed and compared. It was estimated that medium- and less successful, in terms of firm performance, innovation strategies had sprouted, whereas the most successful innovation strategies had been rarefied due to the grown necessity for cost reduction and for greater flexibility. Only a few countries are still leading in developing new products or in significantly changing existing products as they did about 7 years ago. However, the greater part of the sample economies do not follow the old leadership patterns. Even though more and less innovative economies can still be distinguished, the countries comprising more and less innovative clusters have changed.